Sunk cost effects for thee but not for me: Decisions and predictions involving others - Zhiqin Chen; Şule Güney; Richard S. John (Acta Psychologica)
The sunk-cost effect (SCE) refers to the tendency to continue pouring resources into a venture due to unrecoverable prior investments, despite a potentially unfavorable outcome ahead. In the two studies reported here, we aimed to explore the issue of whether the SCE is susceptible to the involvement of others by differentiating the individual who would incur the cost (i.e., self vs. someone close vs. stranger) as well as the modality of the primary decision maker's involvement (i.e., making a decision vs. a prediction vs. a suggestion). To measure the magnitude of the SCE, we used eight vignettes about everyday personal decisions adapted from Strough et al. (2014) in Experiment 1 and developed a new scale with 20 vignettes in Experiment 2. Our main findings showed that predictions indicate a greater SCE than suggestions for someone close and strangers. However, we did not find evidence in either experiment supporting the hypothesis that the SCE would be greater for self than for someone close for either decisions or predictions. We discuss the implications of these findings in terms of five competing interpretations of the SCE, namely, mental accounting, gain-loss framing, wishful thinking, opportunity costs, and conflicting objectives.